Global Policy Responses to the COVID-19 Pandemic: Results of the ICOH Survey - Bruna M. Rondinone; Antonio Valenti; Valeria Boccuni; Erika Cannone; Fabio Boccuni; Diana Gagliardi; Pierluca Dionisi; Caterina Barillari; Sergio Iavicoli (Safety and Health at Work, 2022)
Background: On the basis of its role for the development of occupational health research, information, good practices, the International Commission on Occupational Health (ICOH) launched the present survey to collect information on public health and prevention policies put in place by the governments of the countries in the world to contain the pandemic. Methods: A cross-sectional study was conducted through an online questionnaire focused on COVID-19 data, public health policies, prevention measures, support measures for economy, work, and education, personal protective equipment, intensive care units, contact tracing, return to work, and the role of ICOH against COVID-19. The questionnaire was administered to 113 ICOH National Secretaries and senior OSH experts. Collected data refer to the period ranging from the beginning of the pandemic in each country to June 30, 2020. Results: A total of 73 questionnaires from 73 countries around the world were considered valid, with a 64.6% response rate. Most of the respondents (71.2%) reported that the state of emergency was declared in their country, and 86.1% reported lockdown measures. Most of the respondents (66.7%) affirmed that the use of face masks was compulsory in their country. As for containment measures, 97.2% indicated that mass gatherings (meetings) were limited. Regarding workplace closing, the most affected sector was entertainment (90.1%). Conclusion: The results of this survey are useful to gain a global view on COVID-19 policy responses at country level.